From Perception to Practice: Aligning Self-Reported TPACK with Observed Teaching Performance in Pre-service EFL Teachers - Sulastri Manurung; Sri Setyarini; Susi Septaviana Rakhmawati (LPPM Universitas Advent Indonesia, 2026)
This study aimed to examine the alignment between pre-service EFL teachers’ self-reported Technological Pedagogical Content Knowledge (TPACK) and their observed teaching performance following a Microteaching Lesson Study (MLS) intervention. In response to increasing demands for technology-integrated instruction, concerns persist regarding whether teachers’ perceived competencies accurately reflect their actual teaching practices. A quantitative within-subject experimental design was employed involving 27 pre-service teachers over a 14-week intervention. Data were collected using a pre- and post-test EFL-TPACK survey and performance-based assessments of teaching and re-teaching phases evaluated by two independent raters using a validated TPACK-based rubric. Data were analyzed using paired-samples t-tests, Wilcoxon Signed-Rank Tests, Pearson correlation, and normalized gain (N-gain) analysis. The results revealed a statistically significant improvement in self-reported TPACK (p < .001) with a high N-gain, indicating substantial perceived development. Observed teaching performance also improved significantly (p < .001), both at the overall level and across all TPACK domains. However, correlation analysis showed a very weak and non-significant relationship between self-reported TPACK and observed teaching performance (r = .054, p > .05), indicating a lack of alignment between perceived and enacted competence. These findings suggest that while MLS effectively enhances both perceived knowledge and teaching performance, self-reported TPACK does not necessarily reflect actual instructional ability. This study underscores the importance of integrating performance-based assessments with self-report measures to provide a more accurate evaluation of teacher readiness and contributes to a deeper understanding of TPACK development in practice-based teacher education contexts.